Treatment time for surgical-orthodontic cases: a private versus public setting comparison - Lee Richard J.H; Perera Asanka; Naoum Steven; Duigou Christophe; Rea Alethea; Goonewardene Mithran S. (Sciendo, 2021)
Objective: To evaluate the duration of combined orthodontic and orthognathic surgical cases treated either in the public or private health system in Western Australia.